Influence of temperature upon paralyzing and myotoxic effects of bothropstoxin-I on mouse neuromuscular preparations - Cavalcante, WLG; Silva, MDP; Gallacci, M. (Elsevier B.V., 2005)
Bothropstoxin-I (BthTX-I), from B. jararacussu venom, is a phospholipase A(2) (PLA(2)) homologue devoid of enzymatic activity. Besides inducing severe myonecrosis, BthTX-I promotes paralysis of both directly and indirectly evoked contractions in isolated neuromuscular preparations. We applied an experimental paradigm in order to characterize the steps involved in the toxic effects of BthTX-I on mouse neuromuscular junction. Myotoxicity was assessed by microscopic analysis of extensor digitorum longus muscles; paralyzing activity was evaluated through the recording of isolated contractions indirectly evoked in phrenic-diaphragm preparations. After 90 min at 35 degreesC, BthTX-I induced complete and irreversible paralysis, and damaged 30.3 +/- 2.7% of muscle fibers. In contrast, no effect was observed when tissues were incubated with BthTX-I at 10degreesC for 60 min and subsequently washed with toxin-free solution and maintained at 35 degreesC. These results indicate that the binding of BthTX-I to the cellular tissue surface is very weak at low temperature and that an additional factor is necessary. However, when tissues were submitted to BthTX-I (10degreesC for 60 min), and the temperature was elevated to 35 degreesC, omitting the washing step, it was observed muscle paralysis and damage in 39.04 +/- 4.2% of muscle fibers. These results indicate that a temperature-dependent step is necessary for BthTX-I to promote both its myotoxic and paralyzing activities. (C) 2004 Elsevier B.V.. All rights reserved.
Keywords: bothropstoxin-I; myonecrosis; muscle paralysis; myotoxin; phospholipase A(2); Lys49